Photodynamic therapy with a novel photosensitizer inhibits DSS-induced ulcerative colitis in rats via the NF-κB signaling pathway - Rong, Yumei; Zhu, Minghui; Wang, Nan; Zhang, Feiyu; Liu, Tianjun (Frontiers in Pharmacology, 2025)
IntroductionUlcerative colitis (UC) is an inflammatory bowel disease characterized by inflammation and ulceration of the digestive tract.MethodsPhotodynamic therapy (PDT) with a novel photosensitizer LD4 was used to treat UC rat models to explore the therapeutic effect and mechanism of LD4-PDT on UC. 16S ribosomal RNA was used to detect the composition of Gut microbiota.ResultsOur findings indicate that LD4-PDT could protect the integrity of the colonic mucosa, alleviate the inflammatory response and promote the healing of colonic mucosa. Mechanism studies demonstrated that LD4-PDT could inhibit the NF-κB signaling pathway, downregulated the expression of the inflammatory factors’ tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and myeloperoxidase (MPO), increased the contents of glutathione (GSH) and superoxide dismutase (SOD) and decreased the content of malondialdehyde (MDA). Additionally, analysis of gut microbiota revealed that LD4-PDT treatment could decrease the abundance of the Proteobacteria phylum in fecal samples, while no significant differences were observed in the Firmicutes, Bacteroidetes, or Actinobacteria phyla among the three groups using 16S rRNA analysis.DiscussionIn summary, our data suggested that LD4-PDT could inhibit DSS-induced UC in rats via the NF-κB signaling pathway, indicating its potential as a novel photosensitizer for the treatment of UC.